PROTOTYPE: STANDARD OPERATING PROCEDURE (SOP) FOR NURSING SHIFT HANDOVER IN ADULT ONCOLOGY TREATMENT SERVICES WITHIN A HOSPITAL SETTING (Editora Impacto Científico, 2025)
Introduction: A Standard Operating Procedure (SOP) is an institutional document developed for the standardization of work processes among professionals. Its main function is to optimize time and avoid waste. The development of a Prototype Standard Operating Procedure for the handover of nursing shifts in adult oncology treatment services in the hospital setting was the strategy found for aligning this activity and ensuring the transmission of safe care. It is necessary to pay attention to confidential information related to patients, in accordance with the General Data Protection Law (LGPD). Objectives: To guide and align nursing teams regarding the shift handover activity; ensure the continuity of care provided, promoting care safety; perform early detection of avoidable incidents, and stimulate interaction and harmony among care teams. Methods: Methodological study, to support the construction of a technological product aimed at standardizing shift handovers. In addition to the descriptive/explanatory form, a flowchart was constructed with the necessary content for its execution. Conclusion: The technological production aims to contribute to the nursing care practice in the oncology segment; creating a guide to perform this task provides safety to patients and professionals in the provision of care. The product will be available for applicability in the various existing oncology treatment services.DOI: https://doi.org/10.56238/edimpacto2025.090-059